If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -1(3x + 2x) = 10 Combine like terms: 3x + 2x = 5x 25 + -1(5x) = 10 Remove parenthesis around (5x) 25 + -1 * 5x = 10 Multiply -1 * 5 25 + -5x = 10 Solving 25 + -5x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -5x = 10 + -25 Combine like terms: 25 + -25 = 0 0 + -5x = 10 + -25 -5x = 10 + -25 Combine like terms: 10 + -25 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 16x=32 | | 10x-6=64 | | 3x^2+21x+30= | | -y+18+3y=6+5y | | 4y-3=75-x | | 265-60+5d=330 | | 3x-4=-25 | | y=30x-24x^2 | | 9x^2+25x-6=0 | | 12-(2x+8)=12 | | (x+9)(x+3)= | | 16x^2+10x+1=0 | | 3x+2=x+5 | | x^2-8x=-11 | | R=15 | | x^2+7=-6x | | 5x+2-2x=10x-12 | | (x+4)^2=31 | | 5x+2-2x=10x-2 | | 5x^2+12+6=0 | | -5(x-8)+3x=2(3x-6) | | x^2=361 | | -90+12x=-48x^2 | | .5+4=0.6 | | 2(x+8)=4-(3x+8) | | x(3x+10)=77 | | a=4+8+15/3 | | 9(6x-11)+11=5x+2 | | 3+m+7=19-2m | | a^3-2a^2-3a^2-4a^3= | | 3x+9=5x-12 | | 10x+4-5=0 |